Engineering Antioxidant Surfaces for Titanium-Based Metallic Biomaterials - Jithin Vishnu; Praveenkumar Kesavan; Balakrishnan Shankar; Katarzyna Dembińska; Maria Swiontek Brzezinska; Beata Kaczmarek-Szczepańska (Journal of Functional Biomaterials, 2023)
Prolonged inflammation induced by orthopedic metallic implants can critically affect the success rates, which can even lead to aseptic loosening and consequent implant failure. In the case of adverse clinical conditions involving osteoporosis, orthopedic trauma and implant corrosion-wear in peri-implant region, the reactive oxygen species (ROS) activity is enhanced which leads to increased oxidative stress. Metallic implant materials (such as titanium and its alloys) can induce increased amount of ROS, thereby critically influencing the healing process. This will consequently affect the bone remodeling process and increase healing time. The current review explores the ROS generation aspects associated with Ti-based metallic biomaterials and the various surface modification strategies developed specifically to improve antioxidant aspects of Ti surfaces. The initial part of this review explores the ROS generation associated with Ti implant materials and the associated ROS metabolism resulting in the formation of superoxide anion, hydroxyl radical and hydrogen peroxide radicals. This is followed by a comprehensive overview of various organic and inorganic coatings/materials for effective antioxidant surfaces and outlook in this research direction. Overall, this review highlights the critical need to consider the aspects of ROS generation as well as oxidative stress while designing an implant material and its effective surface engineering.